The Oxford guide to treaties - Hollis, Duncan B. (OUP OxfordGB, 2014)
Provides a comprehensive and current guide to treaty law and practice, including (but not limited to ) issues raised in Vienna Convention on the Law of Treaties (VCLT) and later codification efforts.